NEUROLOGICAL CONTROL AND MONITORING IN SURGICAL CORRECTION OF SEVERE FORMS OF SCOLIOTIC DISEASE - Fathulla R. Umarkhodjaev, (Central Asian Journal of Medicine, 2025)
In this article searched usage of preoperative neurological control and monitoring. Carried out analysis of the problem of neurological complications during elective surgery of severe scoliotic disease forms.